Implementación de un sistema de supervisión, control y simulación para el banco de refrigeración del AEIRNNR. - García Moreno, Iván Patricio (2010)
The automatic control and monitoring are of great importance in our days, we constantly observe that technology pervades all sectors of industry, and as it cannot be otherwisethe refrigeration sector, has not been left out of these advances For this reality with the fundamental purpose of contributing to the teaching-learning process of students and teachers of the Electromechanical Engineering degree, we have planned to perform an investigation and foremost a highly practical work in the field of automation; for this research work was necessary to seek the cooperation of the authorities of the career, specifically in the sense of request a bank (of refrigeration) to execute our work on it. The request was received and it is for this that they facilitated us a bank of existing refrigeration in one of the laboratories. On this is that we went to perfect the work and change the manual mode to automatic mode; using for it some devices and especially appropriate Software. The main goal is through the appropriate units, have a control, reports of operation and system simulation similar to the bank of refrigeration, purpose of our work, as well as other cooling mechanisms